Access to information, price expectations and welfare: the role of mobile phone adoption in Ethiopia - Haile, M.G.; Assfaw Wossen, Tesfamicheal; Kalkuhl, M. (Elsevier, 2019)
Using household survey data from rural Ethiopia, this study explores the role of mobile telephony in smallholder farmers' price expectation formations. The empirical findings suggest that farmers who own mobile phones and who reside closer to markets make smaller price forecasting errors. The beneficial effect of mobile phones is stronger for households that reside farther away from grain markets, indicating that mobile telephony provides information that at least partially compensates location-disadvantaged farmers. Holding all else constant, mobile phone ownership is associated with about a 30% decrease in the conditional mean of a smallholder's price prediction error, whereas an additional kilometer from nearby grain markets reduces the expected prediction error by about 10%. The results are robust across different econometric estimators as well as the use of alternative measurements of price forecasting error. Our simulation analysis shows that accurate information about grain price developments could save a significant welfare loss for smallholders. Depending on their income levels, the analysis hints that smallholder farmers would be willing to pay between 7% and 20% of their income to improve the price signal, in other words, to avoid uncertainty on producer prices. Our work emphasizes an alternative way to deal with price volatility and improve farmers' welfare that focuses on improving access to information rather than reducing volatility per se.